Mixed MXenes: Mo1.33CTz and Ti3C2Tz freestanding composite films for energy storage. (October 2021) - Etman, Ahmed S.; Halim, Joseph; Rosen, Johanna
Abstract: MXenes are a class of 2D materials with outstanding properties, including high electronic conductivity, hydrophilicity, and high specific capacitance. In particular, Mo1.33 CTz MXene has a high specific capacitance, whereas films of Ti3 C2 Tz MXene possess high flexibility and high electronic conductivity. The fabrication of composite materials based on these two MXenes is therefore motivated, taking advantage of combining their good properties. In this article, we introduce a one-step approach to prepare composite MXene films using pristine Mo1.33 CTz and Ti3 C2 Tz MXenes. The composite films display superior flexibility and electronic conductivity, as well as high capacitance, up to 1380 F cm −3 (460 F g −1 ), in 1 M H2 SO4 . A capacitance retention of 96% is obtained after 17, 000 cycles. In addition, the capacitance retentions are about 56% and 25% at scan rates of 200 mV s −1 and 1000 mV s −1, respectively. A significant rise in the capacitance at high rates, 875 F cm −3 (282 F g −1 ) at a current density of 20 A g −1, is achieved by using a 3 M H2 SO4 solution. The use of composite MXene as negative electrodes for asymmetric supercapacitor devices, as well as lithium-ion batteries, is also discussed. This work suggests new pathways for the use of MXene composites with double transition metals (Mo and Ti) in energy storage devices. Graphical Abstract: ga1 Highlights: Simple, fast, and robust synthesis approach to fabricate mixed MXene films using Mo1.33 CTz and Ti3 C2 Tz pristine MXenes. The mixed MXene films display good flexibility and high electronic conductivity (up to 140 S cm −1 ). The mixed MXene films deliver a high capacitance (1380 F cm −3 ) and feature 96% retention after 17, 000 cycles in 1 M H2 SO4 . A significant rise in the rate performance is observed in 3 M H2 SO4 solution (875 F cm −3 at current density 20 A g −1 ). Mixed MXene electrodes are employed as negative electrodes for asymmetric supercapacitor devices.